Gender-related differences in cognitive performance and cognitive stimulation efficacy in subjects with Parkinson’s disease and mild cognitive impairment - Iaccino, Noemi; Buonocore, Jolanda; Torchia, Giusi; Curcio, Francesca; Pirrotta, Fabio M.; Contrada, Marianna; Pignolo, Loris; Gambardella, Antonio; Arabia, Gennarina (Frontiers in Aging Neuroscience, 2025)
BackgroundGender-related differences in cognitive performances of subjects with Parkinson’s Disease and mild cognitive impairment (MCI-PD) have been recently investigated in a few studies, yielding heterogeneous results. Cognitive stimulation (CS) is a promising non-pharmacological treatment in MCI-PD subjects and no data regarding gender differences in its efficacy are available yet. The aim of this study was to investigate gender-related differences in cognitive functions and CS efficacy in subjects with MCI-PD.MethodsForty-five MCI-PD subjects (30 men, 15 women) were randomized to a 4-week CS program, delivered either via tele-rehabilitation (TR) or with a conventional in-person approach. A broad clinical and neuropsychological assessment, including the Cognitive Reserve Index questionnaire, was conducted at baseline (T1), post-treatment (T2), and at 6-month follow-up (T3).ResultsAt baseline, women showed a lower cognitive reserve (CR) compared to men (p = 0.039). After adjusting for CR, women performed worse than men in global cognition, attention, and visuospatial abilities. After CS treatment, men demonstrated significant improvements in global cognition, language, executive functions, working memory, visuospatial abilities, attention, and trait anxiety (p < 0.05). Women showed significant improvements in global cognition (MoCA, p = 0.036) and mood (BDI, p = 0.021). Men outperformed women in several domains, both in TR and in-person rehabilitation groups. Regression models revealed a stronger modulatory effect of CR in global cognition, attention, memory, and language, in women. After a 6-month treatment discontinuation, cognitive performance measures significantly worsened in all subjects, regardless of gender.ConclusionOur study showed gender-related differences both in cognitive functions and in efficacy of CS in subjects with MCI-PD, also highlighting the role of cognitive reserve. These findings support the relevance of developing gender-tailored cognitive rehabilitation strategies to enhance treatment outcomes and improve the quality of life for individuals with MCI-PD.